The dissolution of Dar Es Salaam City Council paradoxes to local governance in Tanzania - Bukurura, Sufian Hemed (1999)
Local government authorities were abolished in 1989 and MacKinsey's decentralized scheme were put in place in 1972. Tanzanians in general and Dar residents in particular, were never consulted as to what form of local government administration would best suit their needs. After the government got dissatisfied with the decentralization system, laws were passed establishing urban authorities including the DCC in 1978 and local authorities in 1982. DCC and other local authorities were, in essence, instituted without the consent of the local populace concerned. Whereas residents of respective authorities have not been appropriately empowered to control their local authorities, the central government has widespread powers of supervision and control but has never exercised them that thoroughly. Not only were the residents been denied the requisite powers which could lead to the successful performance of their local authorities (i.e. DCC) but the central government took it upon itself to do naught. This illustrates an enigma of disproportionate disempowerment of the constituency and oversated control by the central government.
Keywords: Dar Es Salaam City Council (DCC); Local government -- Tanzania; Politics and government -- Tanzania